PENINGKATAN KOMPETENSI GURU DENGAN PENGENALAN MODEL – MODEL DALAM TAHAPAN PENELITIAN TINDAKAN KELAS DI SMK NEGERI KOKAR - Antonius A. Saetban; Alboin Selly; Apnamilsah Obisuru; Yesriel Lelan; Sarah A. Beli; Abdul M. Djou (Yayasan Education and Social Center, 2023)
PTK is a report of real activities carried out by teachers in the classroom in an effort to improve the quality of learning. Classroom Action Research (PTK) is important in improving and improving the profession of educators, it is also important for improving and improving the quality of students. The purpose of this activity is to carry out the Tri Darma of Higher Education activities in the aspect of community service. This activity aims to share knowledge information in the context of developing the competence of teachers at SMK N Kokar. This service activity is carried out using lecture methods and practices. The lecture method was delivered by resource persons with material about Class Action Research (PTK). Furthermore, the practice is carried out directly by the teacher with the practice of making PTK proposals as well as being presented as a form of guidance and evaluation of the stages of research preparation. The result of this PKM activity is that teachers at SMK Neegri Kokar can understand the steps and stages in implementing PTK. In addition, the teachers already have a plan for PTK proposals that will be implemented in the near future. Furthermore, Mr / Mrs. Guru also has a new motive in order to develop themselves to meet the requirements for promotion and teacher certification